Optical coherence tomography for fast bedside imaging, assessment and monitoring of autoimmune inflammatory skin diseases?. (18th September 2020) - Ha, Linh; Hundt, Jennifer E.
Summary: Optical coherence tomography (OCT) is a non‐invasive, high‐resolution imaging technique with a growing impact in dermatology. The principle of OCT is comparable to that of sonography, except that it uses infrared laser light instead of ultrasound waves. It has been clinically demonstrated that OCT is suitable for discriminating between different types of non‐melanoma skin cancer at an early stage of disease. Optical coherence tomography generates two‐ or three‐dimensional images of up to 2 mm penetration depth, a field of view of 6 mm × 6 mm, and an acquisition time of seconds. The resolution capability of OCT is more than 3 to 100 times higher than that of ultrasound imaging. It is of particular interest that the additional information on vasculature provided by OCT angiography enables the assessment and monitoring of inflammatory skin diseases. The use of OCT to locate exact blister levels was demonstrated for diagnosing autoimmune bullous diseases. It is anticipated that detection of subclinical lesions could indicate a relapse of the disease. In the future, this could enable intervention and early treatment. Furthermore, the development of high‐speed OCT could allow fast scanning and bedside imaging of large body sites.